2006
DOI: 10.1021/ja060873e
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Oligonucleotide−Peptide Conjugates with Aggregating Properties Enter Efficiently into Cells while Maintaining Hybridization Properties and Enzymatic Recognition

Abstract: Oligonucleotide delivery is a crucial issue for therapeutical purposes and is often addressed by conjugation to short cationic peptides although with controversial results. To further examine this mechanism, a 15-mer anionic oligonucleotide was conjugated to a cationic peptide in order to obtain a diblock compound with an overall positive charge with aggregation properties. These microaggregates were efficiently internalized in cells via the expeditious pathway used by commercial gene delivery systems. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…8,9 Cationic ONs, which are conjugates of natural phosphodiester (PDE) ON with polycation moieties, such as peptides 10 and polyamines, 11 have been reported. Recently, it was reported that spermine-conjugated PDE ON has higher affinity to complementary strands than natural PDE ON due to the decrease of electrostatic repulsion, 12,13 and also exhibits effective cell penetrating potency by electrostatically anchoring to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Cationic ONs, which are conjugates of natural phosphodiester (PDE) ON with polycation moieties, such as peptides 10 and polyamines, 11 have been reported. Recently, it was reported that spermine-conjugated PDE ON has higher affinity to complementary strands than natural PDE ON due to the decrease of electrostatic repulsion, 12,13 and also exhibits effective cell penetrating potency by electrostatically anchoring to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the employed cationized form of GNPs allows ODN loading onto the surface via electrostatic interactions. Furthermore, the positive charge of the carrier facilitates the cellular uptake of the bound DNA, which, due to its negative charge, cannot penetrate cell membranes on its own (Fraley et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The nucleus-specific green fluorescence dye DAPI (4 0 ,6-diamidino-2-phenylindole, excitement at 470 nm, Promega) was added to each well, and the cells were first incubated for 4 h at 37 C in a 5% CO 2 humidified air atmosphere, and then washed three times with PBS. The cells were visualized not only by fluorescent microscopy using a Leica DMI3000B inverted microscope equipped with epifluorescent illumination using appropriate filter sets, but also by confocal laser scanning microscopy [39,40]. Fluorescent imaging was taken consecutively using the same image acquisition parameters.…”
Section: Cellular Uptake Studymentioning
confidence: 99%